The Dramatic Role of IFN Family in Aberrant Inflammatory Osteolysis - Deng, Zihan; Hu, Wenhui; Ai, Hongbo; Chen, Yueqi; Dong, Shiwu (Current Gene Therapy, 2021)
Skeletal system has been considered a highly dynamic system, in which bone-forming osteoblasts and bone-resorbing osteoclasts go through a continuous remodeling cycle to maintain homeostasis of bone matrix. It has been well acknowledged that interferons (IFNs), acting as a subgroup of cytokines, not only have crucial effects on regulating immunology but also could modulate the dynamic balance of bone matrix. In the light of different isoforms, IFNs have been divided into three major categories in terms of amino acid sequences, recognition of specific receptors and biological activities. Currently, type I IFNs consist of a multi-gene family with several subtypes, of which IFN-α exerts pro-osteoblastogenic effects to activate osteoblast differentiation and inhibits osteoclast fusion to maintain bone matrix integrity. Meanwhile, IFN-β suppresses osteoblast-mediated bone remodeling as well as exhibits inhibitory effects on osteoclast differentiation to attenuate bone resorption. Type II IFN constitutes the only type, IFN-γ, which exerts regulatory effects on osteoclastic bone resorption and osteoblastic bone formation by biphasic ways. Interestingly, type III IFNs are regarded as new members of IFN family composed of four members, including IFN-λ1 (IL-29), IFN-λ2 (IL-28A), IFN-λ3 (IL-28B) and IFN-λ4, which have been certified to participate in bone destruction. However, the direct regulatory mechanisms underlying how type III IFNs modulate the metabolic balance of bone matrix, remains poorly elucidated. In this review, we have summarized functions of IFN family during physiological and pathological conditions and described the mechanisms by which IFNs maintain bone matrix homeostasis via affecting the osteoclast-osteoblast crosstalk. In addition, the potential therapeutic effects of IFNs on inflammatory bone destruction diseases such as rheumatoid arthritis (RA), osteoarthritis (OA) and infectious bone diseases are also well displayed, which are based on the predominant role of IFNs in modulating the dynamic equilibrium of bone matrix.
Keywords: Interferons (IFNs)